Déficit de atención con o sin hiperactividad en alumnos del nivel primario de una institución educativa de Ventanilla - García Calderón, Aida Luz Araníbar (2012)
This research seeks to highlight the characteristics of ADHD The sample was intentional and consisted of primary level students of both sexes from first to sixth grade, aged between 6 and 14 years and which showed characteristics of ADHD in an educational institution Window. The instrument used was a questionnaire created by Keith ConnersConners at (1969) and abridged version of which is dated 2002 which has 20 items. Through the results it was found that attention deficit disorder ADHD occurs more frequently in males, between 6-7 years while in women there was a slight suspicion. It is likely that the lack of concentration and inability to focus attention in boys with ADHD could impede the achievement of learning more than in women with suspected ADHD.